Efforts to Improve the Ability of PKN Subject Teachers in the Use of Learning Aids Through the Implementation of Class Visit Supervision at Yunior High School Cerdas Mandiri - Marpaung, Rince; Silalahi, Jojor; Napitupulu, Herdi Susri (Jurnal Simki Pedagogia, 2024)
The purpose of implementing classroom action research activities is to provide an explanation of the process of implementing class visits as an effort to improve the ability of Civics Subject Teachers using learning teaching aids. This research method is Classroom Action Research with four main steps, namely: action planning, action implementation, observation and reflection. The results showed that the ability of teachers in learning planning using learning aids in the initial condition only reached an average number of 57.58 with less criteria and the first cycle increased to 68.18 in sufficient criteria and in the last cycle to 80.30 in very good criteria, and individually per teacher in the initial condition no teacher was declared complete, increased to 5 teachers or 45.45% and in the last cycle to 100%, and the ability of teachers in the implementation of learning using learning aids in the initial condition only reached an average of 59.22 with less criteria and the first cycle increased to 69.57 in sufficient criteria and in the last cycle to 84.22 in very good criteria, and individually per teacher in the initial condition no teacher was declared complete, increased to 45.45% and in the last cycle to 100%.